Delayed presentation of an undiscovered nasopharyngeal foreign body - Ramdoo, Krishan (BMJ Publishing Group, 2014)
Suspected paediatric aerodigestive tract foreign body (FB) ingestion or aspiration is a commonly encountered emergency. Management may require a general anaesthetic for retrieval with bronchoscopy, laryngoscopy and oesophagoscopy, each dependent on the history and investigations of the case in question. We describe the case of a foreign body, which was missed in the nasopharynx for more than 3 years and also discuss how pressures on National Health Service (NHS) referral and follow-up patterns may have altered the time course of the eventual discovery.